Multistep Structural and Chemical Evaluation of Sugarcane Baggase, Pretreated With Alkali for Enhancing the Enzymatic Saccharification by Cellulase and Xylanase of the Pseudomonas sp. CVB-10 (MK443365) and Bacillus paramycoides T4 (MN370035) Mix-Culture System - Tiwari, Soni; Yadav, Janardan; Gaur, Rajeeva; Singh, Ranjan; Verma, Tuhina; Yadav, Jay Shanker; Pandey, Prabhash Kumar; Rath, Srikanta Kumar (Frontiers in Energy Research, 2022)
The enzymatic saccharification of sugarcane bagasse was significantly increased by alkali pretreatment under mild conditions. The effectiveness of different concentrations of alkali and acid pretreatment of sugarcane bagasse for improving the enzymatic saccharification of lignocellulose has been evaluated. The sugarcane bagasse was characterized to contain 39.52% celluloses, 25.63% hemicelluloses, and 30.36% lignin. After that, sugarcane bagasse was pretreated with 5 and 10% of H2SO4 and NaOH at 121°C for 60 min. FTIR, XRD, and SEM analyses also showed significant molecular and surface structure changes of the sugarcane bagasse with 10% NaOH. Maximum saccharification was 489.5 mg/g from 10% NaOH pretreatment followed by 322.75, 301.25, and 276.6 mg/g from 10% H2SO4, 5% NaOH, and 5% H2SO4, respectively, which were 55.1, 32.0, 27.1, and 20.6 times higher than the that of the control. Cellulase and xylanase produced by Pseudomonas sp. CVB-10 (MK443365) and Bacillus paramycoides T4 (MN370035) were used to hydrolyze the pretreated bagasse, and the optimal condition was determined to be 30 h of the enzymatic reaction with the 3:1 ratio of enzymes under the temperature of 55°C, pH 5.0, and substrate concentration of 3%, leading to celluloses and hemicelluloses conversion in the enzymatic hydrolysis/saccharification that is more proficient.